Analisis Pemilihan Kepala Toko Dengan Menggunakan Metode ROC dan Multi-Objective Optimization on The Basic of Ratio - Oktaria, Intan (Journal of Data Science and Information Systems, 2024)
A Head of Shop is an individual who is responsible for the management of the day-to-day operations of a store. His role includes overseeing staff performance, managing inventory and stock, planning marketing strategies, and ensuring that customers receive satisfactory service. A major problem in Head Store Selection is the difficulty in finding candidates who have a combination of managerial skills, interpersonal expertise, and a deep understanding of the retail industry. This difficulty can result in the selection of a head shop that does not match the needs of the store and even potentially harm the performance and reputation of the store. Choosing a quality head store will have a positive impact on store productivity, customer satisfaction, and overall business profitability. By prioritizing leadership qualities, a store can achieve long-term success in the retail industry. The purpose of this study is to develop a holistic and effective approach in the process of selecting Store Heads using ROC and MOORA weighting methods. The ranking results gave the 1st rank result in the selection of store heads with a final value of 0.4966 obtained by the BY Candidate, this result became a recommendation to the company in determining the head of the store who would be responsible for store operations.